Menggagas âAkuntansi Publik Terintegrasiâ pada Organisasi Sektor Publik - Handajani, Lilik (Jurnal Akuntansi Multiparadigma, 2010)
The objective of this article is to review accounting system and system of accountability at public sector organization post New Public Management (NPM) implementation, that is assumed to have strong capitalism idea.Â  Social interest is often neglected due to political one. It emphasizes on reporting process, accountability, economic and secular performance, and owns disconcern on social and religious value in the practice. Based on Giddenâs structure analysis in interdependency interaction between government agents and structure dominated, there is an opportunity that agents do not merely accept dominating structure, but they can actively participate to reform public organisation by creating new ones that are more cultural, ethical, in local Indonesian context, and focus on real problems in management issues. The idea of integrated public accounting that accomodates economy, social, and religion is an urgent need.